Inclusive higher education through e-learning in Israel and Georgia. : Preliminary results from an ongoing project - Jesus, Ângelo; Araújo, André; Cunha, Maria João (PRATICA - Revista Multimédia de Investigação em Inovação Pedagógica e Práticas de e-Learning, 2022)
Higher Education has seen growth across the world in recent decades. However, there are large asymmetries in terms of access, with specific countries/regions showing marked inequalities of opportunities, especially in population groups that are underrepresented due to socioeconomic status, race, ethnicity, religion, age, gender, disability, or origin geographic location. At the same time, access to the internet has become widespread and has proven its potential as a way of democratizing access to information. The Love.Dist@nce project was created to respond to the needs of Georgia and Israel, with input from European partners, with the aim of promoting inclusive education through distance learning. After 18 months of activity, the project is continuing its course and several reports and support materials have already been created that will serve as a basis for the implementation of pilot curricular units currently in progress, involving teachers, students, and non-teaching staff.